AN ANALYSIS OF UNDERGRADUATE STUDENTS’ DIFFICULTIES IN WRITING DESCRIPTIVE PARAGRAPH OF THE SECOND SEMESTER STUDENTS AT QOMARUDDIN UNIVERSITY - Fauziyatun Ni’mah; Hasbullah Hasbullah (Bajang Institute, 2023)
This research aimed to describe an analysis of the undergraduate students’ difficulties in writing descriptive paragraph. This research was conducted in second semester of Qomaruddin University. The design of this research is a qualitative research. The population is all undergraduate students on English Language Education Study Program at Qomaruddin University.. From the population, the second semester of English Language Education Study Program which consist of 27 students is chosen as the sample of this research. The instrument of the study of the data from test, questionnaire, and interview. The components of writing that are analyzed are generic structure (content), organization, grammar, vocabulary and punctuation The result of this research shows that the second semester students of Qomaruddin University have difficulty in writing descriptive text, the difficulties are difficulties in grammar, vocabulary, punctuation, generic structure (conteent) and oganization. Many of them make mistakes in the verb agreement and tenses in grammar, their vocabulary is still not quite right and the spelling of words is not correct, then punctuation marks such as the use of periods, commas and capital letters are still inaccurate and need to improve. While the factors that cause the students’ difficulties in writing descriptive text are lack of interest, lack of knowledge, lack of proficiency, and almost of students were answered that their environtment was quiet supportive for writing.